2022
DOI: 10.1038/s41598-022-23001-6
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of Chinese women facial skin status with environmental factors and individual lifestyles

Abstract: Geographical, environmental and pollution conditions affect facial skin health, but their effects on skin appearance have not been elucidated. This study aimed to describe the skin barrier and skin tone characteristics of Chinese subjects according to lifestyle and environmental conditions using in vitro measurements. In total, 1092 women aged 22–42 years were recruited from 7 representative Chinese cities. Eight skin parameters (hydration, sebum, pH, transdermal water loss, individual type angle, melanin inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…The skin humidity is nonuniform across the face, with higher values in areas with less body fat (e.g., forehead, nose, and chin) and lower values in areas with more body fat, such as the cheeks . The results are consistent with the mixed, oily skin type with high humidity in the T-shaped area (i.e., forehead and nose) and low humidity in the U-shaped area (i.e., cheeks and chin). , The sensor is also applicable to other human subjects (Table S2) for monitoring humidity changes during the day (Figure S14).…”
Section: Health Monitoring and Skin Characterizationsupporting
confidence: 61%
See 1 more Smart Citation
“…The skin humidity is nonuniform across the face, with higher values in areas with less body fat (e.g., forehead, nose, and chin) and lower values in areas with more body fat, such as the cheeks . The results are consistent with the mixed, oily skin type with high humidity in the T-shaped area (i.e., forehead and nose) and low humidity in the U-shaped area (i.e., cheeks and chin). , The sensor is also applicable to other human subjects (Table S2) for monitoring humidity changes during the day (Figure S14).…”
Section: Health Monitoring and Skin Characterizationsupporting
confidence: 61%
“…41 The results are consistent with the mixed, oily skin type with high humidity in the T-shaped area (i.e., forehead and nose) and low humidity in the U-shaped area (i.e., cheeks and chin). 42,43 The sensor is also applicable to other human subjects (Table S2) for monitoring humidity changes during the day (Figure S14).…”
Section: ■ Electromechanical Characterization Of the Humidity Sensormentioning
confidence: 99%
“…41 Furthermore, a cross-sectional study of 1092 women (aged 22-42) from seven cities across China, observed that women from more highly polluted cities had impaired barrier function and darker skin tone. 42 Finally, very briefly, other factors that may contribute to pigmentation issues in Asian patients include smoking, 43 hormones, 33 skin inflammation, medication, and surgical procedures. 44…”
Section: Other Contributing Factors To Photoaging and Pigmentary Diso...mentioning
confidence: 99%
“…Similarly, men living in Baoding had more severe aging signs and were perceived as being older compared to men living in Dalian 41 . Furthermore, a cross‐sectional study of 1092 women (aged 22–42) from seven cities across China, observed that women from more highly polluted cities had impaired barrier function and darker skin tone 42 …”
Section: Asian Skin Is More Prone To Pigmentary Disorders From Sun Ex...mentioning
confidence: 99%
“…Diets high in salt, spices and extremely vegetarian diets are also considered harmful to skin health [13]. The use of cosmetic products also affects skin biophysical parameters [14].…”
Section: Introductionmentioning
confidence: 99%